2020
DOI: 10.1029/2020jb020076
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthal Anisotropy of the Crust and Uppermost Mantle Beneath Alaska

Abstract: This study presents an azimuthally anisotropic shear wave velocity model of the crust and uppermost mantle beneath Alaska, based on Rayleigh wave phase speed observations from 10 to 80 s period recorded at more than 500 broadband stations. We test the hypothesis that a model composed of two homogeneous layers of anisotropy can explain these measurements. This "Two-Layer Model" confines azimuthal anisotropy to the brittle upper crust along with the uppermost mantle from the Moho to 200 km depth. This model pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
45
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 59 publications
8
45
0
Order By: Relevance
“…Fast orientations of shear wave splitting axis across Alaska constitute a toroidal pattern (e.g., Hanna & Long, 2012;Venereau et al, 2019), consistent with the geodynamical modeling (e.g., Haynie & Jadamec, 2017;Jadamec & Billen, 2010). The toroidal mantle flow pattern is also confirmed by a recent surface wave tomography study (Feng et al, 2020), in which the authors further suggested that the vast majority regions across Alaska undergo vertically coherent mantle deformation from the Moho to a depth deeper than 200 km.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Fast orientations of shear wave splitting axis across Alaska constitute a toroidal pattern (e.g., Hanna & Long, 2012;Venereau et al, 2019), consistent with the geodynamical modeling (e.g., Haynie & Jadamec, 2017;Jadamec & Billen, 2010). The toroidal mantle flow pattern is also confirmed by a recent surface wave tomography study (Feng et al, 2020), in which the authors further suggested that the vast majority regions across Alaska undergo vertically coherent mantle deformation from the Moho to a depth deeper than 200 km.…”
supporting
confidence: 77%
“…However, future work is needed to continue to improve resolution of the model, particularly near the Aleutian trench line where the North American plate overriding the incoming Pacific slab. Other fertile directions to pursue in order to improve and extend the model is to infer seismic anisotropy, including azimuthal and radial anisotropy (e.g., Feng et al., 2020; Feng & Ritzwoller, 2019), which could yield more information about the physical properties of the plate and help us better understand the link between plate attributes and seismic behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From Rayleigh waves, Feng et al. (2020) measure upper mantle anisotropy fast directions and show a toroidal pattern around the subducting Yakutat slab in the Denali segment. This toroidal pattern was interpreted as clockwise flow around the Denali segment subducting slab, as predicted by geodynamic models (e.g., Jadamec & Billen, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, due to the near‐vertical incidence of the XKS phases, the depth of the source of the observed XKS splitting remains ambiguous. Fifth, some aspects of the mantle flow systems in the slab edge region, including the lateral extent of the toroidal flow and the existence or absence of an eastward continuation of the sub‐slab flow after it comes out of the slab edge, are still not well understood (Feng et al., 2020; Hanna & Long, 2012; Jadamec & Billen, 2010; Venereau et al., 2019).…”
Section: Previous Sws Studies and Rationale Of The Present Studymentioning
confidence: 99%